Role of Pharmacology in self medication practices among undergraduate medical students in a medical college and hospital in North India - Jindal, Sanchali; Garg, Preeti (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Self medication is an important component of primary health care. It involves treatment of common ailments on ones own initiative or on the advice of a pharmacist. With the easy accessibility to information regarding use of drugs, there is an alarming increase in the self medication practices. Medical students, during their course of study gain considerable knowledge of drugs and it may have an influence on their self medication practices. The present study was designed to gather the knowledge, attitude and behavior of medical students towards self medication and whether an increased knowledge of drugs further promoted self medication. Methods: A questionnaire based study was carried out on students of 2nd semester students relating to their knowledge, attitude and practice of self medication. Results: Though the knowledge regarding drugs is quite comparable in both the first and third year medical students, 39% students in group A took the medicine without doctors’ advice in the last month whereas 58% 5th semester students in group B did the same. Conclusions: The frequency of self medication is higher among third year students as they believe that the medical training makes them capable enough to self medicate easily without any harm. Hence, there is need to promote rational self medication practice to bring awareness about irresponsible self medication.